Water Kefir Kulit Buah Naga: Pengaruh dari Starter dan Lama Fermentasi - Anjliany, Meysin; Pangesti, Ramadhannie Fitra; Mualim, Ilham Akbar (Seminar Nasional Lahan Suboptimal, 2022)
Anjliany M, Pangesti RF, Mualim IA. 2022. Water kefir containing dragon fruit skin: effect of starter and fermentation time. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 660-673. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Utilization of red dragon fruit peels in water kefir making was one kind of optimizing dragon fruit by-products in the diversification of probiotic functional drinks. This study aimed to determine the effect of the algae crystal starter concentration and fermentation time on the physical, chemical, and microbiological characteristics of red dragon fruit peels water kefir. This study used a factorial Completely Randomized Design and significantly different treatments were tested using a further test of 5% level of Honest Significant Difference. Parameters observed were total phenol, antioxidant activity, total titrated acid, total dissolved solids, pH, total lactic acid bacteria, total plate count and qualitative phytochemical screening. The results showed that the fermentation time significantly affected the total phenol value, antioxidant activity, total acid, dissolved solids, pH, and total lactic acid bacteria. Water kefir fermented with 10% starter concentration for 24 hours had the highest antioxidant activity expressed in %IC50. Meanwhile, fermented water kefir with 5% starter concentration for 12 hours showed the lowest antioxidant activity. A2B2 treatment was chosen as the best treatment with a total phenol value of 0.0969 mg/GAE mL, the lowest IC50 value 53.96%, total acid 0.21%, soluble solids 9.57ºBrix, pH 4.4, total lactic acid bacteria 7.27 log CFU /mL.